Помогите пожалуйста! [latex]( \frac{a+2b}{b-a} - \frac{8 a^{2}-8 b^{2} }{ a^{3}- b^{3} } : \frac{4a+4b}{ a^{2} +ab+ b^{2} }):a+ \frac{2b+a}{a-b} [/latex]

Помогите пожалуйста! [latex]( \frac{a+2b}{b-a} - \frac{8 a^{2}-8 b^{2} }{ a^{3}- b^{3} } : \frac{4a+4b}{ a^{2} +ab+ b^{2} }):a+ \frac{2b+a}{a-b} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]( \frac{a+2b}{b-a} - \frac{8 a^{2}-8 b^{2} }{ a^{3}- b^{3} } : \frac{4a+4b}{ a^{2} +ab+ b^{2} }):a+ \frac{2b+a}{a-b} =[/latex][latex]=( \frac{a+2b}{b-a} - \frac{{8 (a- b)(a+b)} }{ (a-b)(a^2+ab+b^2) } : \frac{4(a+b)}{ a^{2} +ab+ b^{2} }):a+ \frac{2b+a}{a-b} = [/latex][latex]=( \frac{a+2b}{b-a} - \frac{{8 (a- b)(a+b)} }{ (a-b)(a^2+ab+b^2) } * \frac{a^{2} +ab+ b^{2} }{ 4(a+b)}):a+ \frac{2b+a}{a-b} = [/latex][latex]=( \frac{a+2b}{b-a} - 2 } ):a+ \frac{2b+a}{a-b} = \frac{a+2b-2b+2a}{b-a} :a+ \frac{2b+a}{a-b} = \frac{3a}{b-a} * \frac{1}{a} + \frac{2b+a}{a-b} = [/latex][latex]= \frac{3}{b-a} + \frac{2b+a}{a-b} = \frac{-3}{a-b} + \frac{2b+a}{a-b} = \frac{2b+a-3}{a-b} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы